2006
DOI: 10.1002/jcu.20232
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic appearance of the uterine cavity following administration of mifepristone and misoprostol for termination of pregnancy

Abstract: An intrauterine echogenic mass with well-defined borders, with or without Doppler flow signals, can be detected 2 weeks after administration of mifepristone and misoprostol for termination of pregnancy. Because most of the women in our study regained normal menses without further surgical intervention, this finding could indicate remnants of trophoblastic tissue evacuated spontaneously from the uterine cavity. Therefore, dilatation and curettage should be avoided in these cases, unless clinical symptoms or sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
0
14
0
3
Order By: Relevance
“…They (31) concluded that this intrauterine abnormality may represent normal physiologic response following medical abortion with mifepristone.…”
Section: Endometrial Width [Mm]mentioning
confidence: 98%
See 1 more Smart Citation
“…They (31) concluded that this intrauterine abnormality may represent normal physiologic response following medical abortion with mifepristone.…”
Section: Endometrial Width [Mm]mentioning
confidence: 98%
“…Markovitch et al (31) described the sonographic appearance of the uterine cavity after mifepristone and found an echogenic mass with well-defi ned borders with or without Doppler fl ow signals up to 2 weeks after treatment. They (31) concluded that this intrauterine abnormality may represent normal physiologic response following medical abortion with mifepristone.…”
Section: Endometrial Width [Mm]mentioning
confidence: 99%
“…They concluded that this finding could indicate remnants of trophoblastic tissue that will pass spontaneously without the need for dilatation and curettage. 10 The major arguments for encouraging histological examination of tissue removed at termination of pregnancy or surgical evacuation of the uterus are to confirm the pre-operative diagnosis, identify unexpected pathology and ensure that a pregnancy does not remain undisturbed. Routine submission of tissue collected at the time of surgery does not reliably confirm or correct the pre-operative diagnosis; neither ensures that the uterus is empty following the surgery nor that a pregnancy has not been effectively surgically terminated.…”
Section: Vidyasagar V Int J Reprod Contracept Obstet Gynecol 2015 Ocmentioning
confidence: 99%
“…In the absence of clinical symptoms, surgical intervention for these ultrasound findings is not indicated, as prevention of future morbidity is unproven. [8][9][10] Many studies have concluded that most of the women regained normal menses without further surgical intervention following diagnosis of failed medical abortion, suggesting that remnants of trophoblastic tissue get spontaneously evacuated from the uterine cavity. 4,10 There is no agreement about the value of submitting tissue for histological examination obtained at uterine curettage in suspected cases of RPOC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation